Factors Influencing the Implementation of Fraud Prevention in Indragiri Hulu District Government - Kadir, Siti Naimah; Ratnawati, Vince; Silvi, Alfiati (International Journal of Economics Development Research (IJEDR), 2024)
Fraud prevention by local governments is essential to fulfill the mandate of Law Number 28 of 1999 in establishing a governance system free from corruption, collusion, and nepotism. Fraud prevention encompasses several objectives, including prevention, deterrence, disruption, identification, and civil action prosecution. This study aims to identify the factors influencing fraud prevention within the Indragiri Hulu district government. The research focuses on organizational units (OPD) within the district government, using a purposive sampling method with a sample of 169 respondents. The findings indicate that governance plays a significant role in fraud prevention, supported by compliance with accounting regulations, the competency of government apparatus, and the implementation of effective risk management practices. These factors collectively contribute to enhancing the capacity of the local government to prevent fraud. The study underscores the importance of governance structures, adherence to financial rules, skills development among government personnel, and risk management as critical elements for achieving transparent and accountable administration. This research provides valuable insights for policymakers and public administrators in strengthening institutional frameworks and practices to reduce the risk of fraud, promoting a cleaner and more efficient public sector.